(3GdLOjO aj GdYdGeGJ GdJLGQjI (B:s (3aj VhA bGfhf MeGjI Mbhb GdedcjI GdacQjI GdLOjO hGJaGbjI GdJQHS (B/s - (3GdUZjQ, MSGe GdOjf YHO GdZfjs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2004)
(3JWhQ MeGjI GdYdGeI GdJLGQjI aj GdEJaGbjGJ GdOhdjI,GdCMcGe GdLOjOI ddYdGeI GdJLGQjI aj bGfhf MeGjI Mbhb GdedcjI GdacQjI GdLOjO,ETQGa efXeI GdJLGQI GdYGdejI Ydi JfajP GdOhd GdCYVGA dGJaGbjI GdJQHSs
Keywords: (3GdYdGeGJ GdJLGQjI(B-(3bhGfjf h JTQjYGJ s; (3Mbhb GdJCdja h GdfTQ s